DETERMINASI DAYA SAING AGROINDUSTRI LIDAH BUAYA DI KOTA PONTIANAK - Alfath Desita Jumiar Alfath; Heny K. Daryanto; Lukman M. Baga (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
This research aims to identify the determinant factors of the competitiveness of aloe vera agroindustry and formulate priority strategies to improve the competitiveness of aloe vera agroindustry in Pontianak Municipality. The study was conducted in Pontianak Municipality as a center of production of Aloe vera in Indonesia. Primary data were collected from processing aloe vera in the packaging and experts from academia and bureaucracy by conducting interviews and questionnaires, while secondary data sourced from CBS, Ministry of Industry, Department of Agriculture, and Aloe Vera Center. The research objectives were answered by using Analytical Hierarchy Process (AHP) with used Porter's Diamond approaches. Data was obtained from expert by filling out a questionnaire in the form of pairwise comparisons assessment, and it was processed by using Expert Choice software. The AHP analysis results showed that the factors determining the competitiveness of aloe vera the agroindustries with the highest weight are the demand condition factor (0.420) and the condition of resources (0.300). Priority strategies that can be done is to manufacture products in accordance with market demand for quality local, national and international (0.196), and creating innovation products for all segments of demand (0.190). Actors who play role directly in an attempt to increase the competitiveness of the aloe vera agroindustries in Pontianak Municipality is private sector such as entrepreneurs and aloe vera farmers (0.634). To achieved the competitiveness improvement of aloe vera agroindustry in Pontianak Municipality, can be repairs such as the quality and type of product, packaging design, and market segments, with the way local government is actively provide guidance and training to the processing of aloe vera and support the establishment of cooperative aloe vera in Pontianak